Preparation method of perovskite solar cell based on mixed ionic liquid additive

By using a hybrid ionic liquid additive during the preparation of perovskite solar cells to regulate the nucleus and growth of olty orthopedic ore, it solves the problem of high density density of perovskite film in the scratch and coating. Density and excellent photoelectric characteristics.

CN119384142AActive Publication Date: 2025-01-28NANKAI UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411297922.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-01-28
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

Existing wide-bandgap perovskite solar cells prepared based on scraping coating method have problems such as difficulty in controlling perovskite nucleation and crystallization, high thin film defect density, and limited research on ionic liquid materials.

Method used

Adopt mixed ionic liquid additives, including imidazole acetate and 1-clone-3-methylimramidazole tetrafluorosilicate, introduce the anterior ore anterior driver solution, and enhance the cationic and perovskite PB through π-π interaction. -The interaction between frameworks, regulate the nuclear and growth of the perovskite crystal.

Benefits of technology

Effective suppression of the formation of the intermediate phase in the crystallization process of perovskite, reducing the deficiency density of the perovskite film, improving the photoelectric characteristics, and simplifying the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384142A_ABST
    Figure CN119384142A_ABST
Patent Text Reader

Abstract

A preparation method of a perovskite solar cell based on a mixed ionic liquid additive relates to the technical field of solar cells, and the cell structure sequentially comprises a transparent conductive substrate, a double hole transport layer, a perovskite light absorption layer, an interface modification layer, an electron transport layer, a buffer layer and a metal electrode from bottom to top. The invention provides a novel mixed ionic liquid additive for the cell, which comprises imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, and is prepared by introducing the imidazole acetate and the 1-butyl-3-methylimidazolium tetrafluoroborate into a perovskite precursor solution. The pi-pi interaction between the imidazole cation and the 1-butyl-3-methylimidazole cation is utilized to enhance the interaction between the cation and a perovskite Pb-I frame, and the formation of an adverse intermediate phase in the perovskite crystallization process is effectively inhibited. Therefore, a single crystallization approach from the NMP + PbI2 intermediate phase to the alpha-perovskite is realized. According to the method, perovskite body phase defects are reduced, the crystallization quality of alpha-perovskite is improved, and the photoelectric conversion efficiency of the solar cell is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cells, and in particular to a method for preparing a mixed ionic liquid additive, comprising imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, to synergistically passivate a wide bandgap perovskite solar cell. Background Art

[0002] In the past decade, significant progress has been made in the field of perovskite solar cells (PSCs), bringing the power conversion efficiency (PCE) to a new level. Wide-bandgap perovskite materials can be used as top cells in tandem cells to improve the utilization of the solar spectrum and further improve the photoelectric conversion efficiency. However, due to the characteristics of perovskite materials, a large number of defects will inevitably form at the grain boundaries and surfaces during the film formation of multi-component perovskites. In addition, most of the preparation methods of high-efficiency PSCs reported so far are limited to laboratory-scale spin coating. In order to promote the transition of PSCs to commercial applications, the development of scalable deposition technology has become an important task.

[0003] Blade coating has been shown to be a low-cost and scalable manufacturing technology, and some progress has been made in the fabrication of PSCs devices. However, the inherent fluid dynamics complexity of the blade coating process poses a major challenge to effectively control the nucleation and crystallization of perovskites, resulting in device efficiencies that are generally lower than those of devices prepared by spin coating. Therefore, further research is needed to develop effective strategies to control the crystallization kinetics of wide-bandgap perovskites during the coating process.

[0004] In order to overcome the above problems, a large number of passivation strategies have been reported. The introduction of non-volatile additives with suitable functional groups not only helps to precisely control the nucleation and crystallization process of perovskite, but also effectively alleviates perovskite defects. Many materials, such as polymers, organic salts, and ionic liquids, are often used as additives to improve the efficiency and stability of perovskite devices. Ionic liquids have low vapor pressure and excellent thermal stability, and can effectively regulate the crystallization process from perovskite precursor solution to film formation. However, there is limited research on strategies for controlling the crystallization kinetics of perovskite using ionic liquids during coating deposition.

[0005] In summary, the problems of preparing organic-inorganic hybrid wide-bandgap perovskite solar cells based on the doctor blade coating method can be summarized as follows: 1) It is difficult to effectively control the nucleation and crystallization of perovskite during the coating process. 2) The defect density of perovskite films prepared by the doctor blade coating method is still very high. 3) There is limited research on ionic liquid materials used to passivate the crystallization process of perovskite prepared by the doctor blade coating method. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned deficiencies in the prior art and provide a method for preparing a perovskite solar cell based on a mixed ionic liquid additive.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a perovskite solar cell with a mixed ionic liquid additive. The cell is a PIN structure, which includes a transparent conductive substrate, a hole transport layer, a perovskite light absorption layer, an interface modification layer, an electron transport layer, a buffer layer and a metal electrode from bottom to top. The band gap of the perovskite solar cell is 1.6 to 1.72 eV.

[0009] The perovskite light absorbing layer satisfies the following conditions simultaneously:

[0010] The perovskite light absorption layer is an organic-inorganic hybrid multi-halogen mixed perovskite;

[0011] The thickness of the perovskite light absorption layer is 500nm-1μm;

[0012] The additive materials are imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, and their chemical formulas are shown in Formula 1 and Formula 2:

[0013]

[0014]

[0015] The additive is introduced into the perovskite precursor solution to passivate the bulk phase of the perovskite light absorbing layer.

[0016] In some embodiments, the transparent conductive substrate is selected from one of FTO conductive glass and ITO conductive glass.

[0017] In some embodiments, the material of the hole transport layer is selected from self-assembled monolayer, P3CT-N, NiO x One or more organic or inorganic hole transport materials;

[0018] The self-assembled monolayer comprises one or more of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, and (2-(7H-dibenzocarbazole-7-yl)ethyl)phosphonic acid self-assembled monolayer.

[0019] In some embodiments, the interface modification layer includes one or more of PEAI, MAI, bis(2-hydroxyethyl)dimethylammonium chloride, and choline chloride.

[0020] In some embodiments, the material of the electron transport layer (5) is selected from PCBM, C 60 One of them.

[0021] In some embodiments, the material of the buffer layer is selected from one of BCP and SnO2.

[0022] In some embodiments, the metal electrode satisfies the following conditions simultaneously:

[0023] The metal electrode is a metal electrode prepared by a thermal evaporation process;

[0024] The thickness of the metal electrode is 50-120 nm.

[0025] In some embodiments, the metal electrode is preferably Ag, Cu, or Au.

[0026] In some embodiments, the method for preparing the perovskite light absorbing layer is a one-step doctor blade method, wherein an ionic liquid additive including imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate is mixed, introduced into a perovskite precursor solution to passivate the perovskite bulk phase, and a wet film of the perovskite absorbing layer is prepared by the one-step doctor blade method, and annealed to obtain the perovskite light absorbing layer.

[0027] In some embodiments, the method for preparing the additive comprises:

[0028] mixing imidazolium acetate and 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquids with a perovskite precursor solution;

[0029] The solvent in the perovskite precursor solution is one or more of dimethylformamide, methyl pyrrolidone, and dimethyl sulfoxide;

[0030] The solute in the perovskite precursor solution is one or more of CsI, MAI, FAI, PbI2, and PbBr2.

[0031] In some embodiments, during the doctor blade coating operation, the nitrogen purge pressure is set to 0.15-0.2 MPa.

[0032] In some embodiments, the annealing operation is performed at a temperature of 100 to 150° C. and a time of 20 to 30 min.

[0033] Furthermore, the present invention provides an application of a perovskite light absorbing layer prepared by the above method, wherein the perovskite light absorbing layer is suitable for a perovskite-based tandem solar cell, and comprises at least the following structural devices:

[0034] 1) Inorganic perovskite / perovskite tandem solar cells;

[0035] 2) Inorganic perovskite / crystalline silicon tandem solar cells;

[0036] 3) Inorganic perovskite / copper indium gallium selenide tandem solar cells.

[0037] Advantages and positive effects of the present invention:

[0038] 1. The present invention proposes a method for preparing a perovskite solar cell based on a mixed ionic liquid additive, by adding two ionic liquids, imidazolium acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, into a perovskite precursor solution to regulate the nucleation and growth of perovskite crystals, thereby improving the quality of the perovskite film.

[0039] 2. The present invention utilizes the π-π interaction between the imidazolium cation and the 1-butyl-3-methylimidazolium cation to enhance the interaction between the cation and the perovskite Pb-I framework, thereby reducing the disorder of the Pb-I structure and effectively inhibiting the formation of unfavorable intermediate phases during the perovskite crystallization process. This method effectively eliminates the occurrence of stacking defects during the transformation of the δ-perovskite intermediate to the α-perovskite, thereby ensuring that the α-perovskite has a lower defect density and excellent photoelectric properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 Schematic diagram of the structure of the perovskite solar cell described in Example 1; in the figure: 1 is a transparent conductive substrate, 2 is a hole transport layer, 3 is a perovskite light absorption layer, 4 is an interface modification layer, 5 is an electron transport layer, 6 is a buffer layer, and 7 is a metal electrode;

[0041] Figure 2 is the JV curve of the perovskite solar cell described in Example 1;

[0042] Figure 3 is the JV curve of the perovskite solar cell described in Example 2;

[0043] Figure 4 The JV curve of the perovskite solar cell described in Comparative Example 1;

[0044] Figure 5 The SEM images of the perovskite light absorbing layers described in Comparative Example 1 and Examples 1 and 2;

[0045] Figure 6 XRD diagrams of the perovskite light absorption layer corresponding to Examples 1 and 2 and Comparative Example 1; DETAILED DESCRIPTION

[0046] The technical scheme of the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are provided in order to further understand the present invention better, are not limited to the best mode of implementation, and do not limit the content and protection scope of the present invention. If no specific experimental steps or conditions are indicated in the examples, the operation or conditions of the conventional experimental steps described in the documents in this area can be carried out. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0047] The present invention provides a perovskite solar cell based on a mixed ionic liquid additive. The cell is a PIN structure and comprises, from bottom to top, a transparent conductive substrate (1), a hole transport layer (2), a perovskite light absorption layer (3), an interface modification layer (4), an electron transport layer (5), a buffer layer (6) and a metal electrode (7); wherein the thickness of the perovskite light absorption layer (3) is 500nm-1μm, and the following conditions are met at the same time: the perovskite light absorption layer (3) is an organic-inorganic hybrid multi-halogen mixed perovskite.

[0048] The additives are imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, which are introduced into the perovskite precursor solution to passivate the perovskite bulk phase. The chemical formulas of imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate are shown in Formula 1 and Formula 2:

[0049]

[0050] Example 1

[0051] The band gap of a PIN-type perovskite solar cell provided in this embodiment is about 1.68 eV, and the structure is as follows Figure 1 As shown, from bottom to top, it includes: a transparent conductive substrate, NiO x (HTL), P3CT-N (HTL), perovskite light absorption layer, BDAC (interface modification layer), PCBM (ETL), BCP (buffer layer), silver electrode.

[0052] The PIN-type perovskite solar cell of this embodiment is prepared by a one-step scraping method, including the following steps:

[0053] Step 1: Pretreatment of transparent conductive substrate: ultrasonically clean the ITO conductive glass with detergent, deionized water, acetone and isopropanol in sequence, blow dry with nitrogen, and treat with ultraviolet ozone for 15-20 minutes.

[0054] Step 2: Preparation of hole transport layer: (1) Spin coating NiO on the ITO surface xsolution as a hole transport layer; (2) annealing at 130°C for 10 min; (3) transferring to a N2 glove box and spin coating P3CT-N on the NiOx surface as a double hole transport layer; (4) annealing at 100°C for 10 min.

[0055] Step 3: Preparation of perovskite light absorption layer: (1) Preparation of 1.6M Cs x FA 1-x Pb(I y Br 1-y )3 perovskite precursor solution; (2) dissolving imidazole acetate in the perovskite precursor solution; (3) preparing a perovskite wet film by a one-step doctor blade coating method using the perovskite precursor solution obtained in step (2); (4) rapidly annealing the obtained wet film at 130°C for 30 minutes and cooling to room temperature to obtain a perovskite light absorbing layer.

[0056] Step 5, preparing an interface modification layer: spin coating a BDAC solution on the surface of the perovskite as an interface modification layer.

[0057] Step 6, preparing an electron transport layer: preparing a PCBM layer on the surface of the interface modification layer as an electron transport layer.

[0058] Step 7, preparing a buffer layer: preparing a BCP layer as a buffer layer on the surface of the electron transport layer.

[0059] Step 8, preparing a metal electrode: preparing a metal silver electrode on the surface of the buffer layer.

[0060] Step 9, photovoltaic performance test: The effective area of ​​the perovskite solar cell device prepared by the above method is 0.0755cm 2 , at 100mW / cm 2 The measurement was performed under light intensity (AM 1.5G), the scanning interval was from 1.3V to 0V, and the scanning step was 0.02V.

[0061] The JV characteristic curve of the obtained perovskite solar cell is as follows Figure 2 As shown by Figure 2 It can be seen that the open circuit voltage of the perovskite solar cell is 1.17V, the fill factor is 79.71%, and the short circuit current density is 19.68mA / cm 2 , the photoelectric conversion efficiency is 18.40%.

[0062] Example 2

[0063] The band gap of a PIN-type perovskite solar cell provided in this embodiment is about 1.68 eV, and the structure is as follows Figure 1 As shown, from bottom to top, it includes: a transparent conductive substrate, NiO x(HTL), P3CT-N (HTL), perovskite light absorption layer, BDAC (interface modification layer), PCBM (ETL), BCP (buffer layer), silver electrode.

[0064] The PIN-type perovskite solar cell of this embodiment is prepared by a one-step scraping method, including the following steps:

[0065] Step 1: Pretreatment of transparent conductive substrate: ultrasonically clean the ITO conductive glass with detergent, deionized water, acetone and isopropanol in sequence, blow dry with nitrogen, and treat with ultraviolet ozone for 15-20 minutes.

[0066] Step 2: Preparation of hole transport layer: (1) Spin coating NiO on the ITO surface x solution as a hole transport layer; (2) annealing at 130°C for 10 min; (3) transferring to a N2 glove box and spin coating P3CT-N on the NiOx surface as a double hole transport layer; (4) annealing at 100°C for 10 min.

[0067] Step 3: Preparation of perovskite light absorption layer: (1) Preparation of 1.6M Cs x FA 1-x Pb(I y Br 1-y )3 perovskite precursor solution; (2) dissolving imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate in the perovskite precursor solution; (3) preparing a perovskite wet film by a one-step doctor blade coating method using the perovskite precursor solution obtained in step (2); (4) rapidly annealing the obtained wet film at 130°C for 30 minutes and cooling to room temperature to obtain a perovskite light absorption layer.

[0068] Step 5, preparing an interface modification layer: spin coating a BDAC solution on the surface of the perovskite as an interface modification layer.

[0069] Step 6, preparing an electron transport layer: preparing a PCBM layer on the surface of the interface modification layer as an electron transport layer.

[0070] Step 7, preparing a buffer layer: preparing a BCP layer as a buffer layer on the surface of the electron transport layer.

[0071] Step 8, preparing a metal electrode: preparing a metal silver electrode on the surface of the buffer layer.

[0072] Step 9, photovoltaic performance test: The effective area of ​​the perovskite solar cell device prepared by the above method is 0.0755cm 2 , at 100mW / cm 2 The measurement was performed under light intensity (AM 1.5G), the scanning interval was from 1.3V to 0V, and the scanning step was 0.02V.

[0073] The JV characteristic curve of the obtained perovskite solar cell is as follows Figure 3 As shown by Figure 3 It can be seen that the open circuit voltage of the perovskite solar cell is 1.21V, the fill factor is 84.89%, and the short circuit current density is 19.44mA / cm 2 , the photoelectric conversion efficiency is 20.12%.

[0074] Comparative Example 1

[0075] The band gap of a PIN-type perovskite solar cell provided is about 1.68 eV, and the structure is as follows Figure 1 As shown, from bottom to top, it includes: a transparent conductive substrate, NiO x (HTL), P3CT-N (HTL), perovskite light absorption layer, BDAC (interface modification layer), PCBM (ETL), BCP (buffer layer), silver electrode.

[0076] The PIN-type perovskite solar cell of this embodiment is prepared by a one-step scraping method, including the following steps:

[0077] Step 1: Pretreatment of transparent conductive substrate: ultrasonically clean the ITO conductive glass with detergent, deionized water, acetone and isopropanol in sequence, blow dry with nitrogen, and treat with ultraviolet ozone for 15-20 minutes.

[0078] Step 2: Preparation of hole transport layer: (1) Spin coating NiO on the ITO surface x solution as a hole transport layer; (2) annealing at 130°C for 10 min; (3) transferring to a N2 glove box and spin coating P3CT-N on the NiOx surface as a double hole transport layer; (4) annealing at 100°C for 10 min.

[0079] Step 3: Preparation of perovskite light absorption layer: (1) Preparation of 1.6M Cs x FA 1-x Pb(I y Br 1-y )3 perovskite precursor solution; (2) preparing a perovskite wet film by a one-step doctor blade coating method using the perovskite precursor solution obtained in step (1); (3) rapidly annealing the obtained wet film at 130°C for 30 minutes and cooling to room temperature to obtain a perovskite light absorbing layer.

[0080] Step 5, preparing an interface modification layer: spin coating a BDAC solution on the surface of the perovskite as an interface modification layer.

[0081] Step 6, preparing an electron transport layer: preparing a PCBM layer on the surface of the interface modification layer as an electron transport layer.

[0082] Step 7, preparing a buffer layer: preparing a BCP layer as a buffer layer on the surface of the electron transport layer.

[0083] Step 8, preparing a metal electrode: preparing a metal silver electrode on the surface of the buffer layer.

[0084] Step 9, photovoltaic performance test: The effective area of ​​the perovskite solar cell device prepared by the above method is 0.0755cm 2 , at 100mW / cm 2 The measurement was performed under light intensity (AM 1.5G), the scanning interval was from 1.3V to 0V, and the scanning step was 0.02V.

[0085] The JV characteristic curve of the obtained perovskite solar cell is as follows Figure 4 As shown by Figure 4 It can be seen that the open circuit voltage of the perovskite solar cell is 1.11V, the fill factor is 73.81%, and the short circuit current density is 19.52mA / cm 2 , the photoelectric conversion efficiency is 16.03%.

[0086] The SEM images of the perovskite solar film obtained in Comparative Example 1, Examples 1 and 2 are as follows: Figure 5 As shown, the synergistic passivation of the two ionic liquid additives significantly improved the surface morphology of the perovskite film.

[0087] The XRD patterns of the perovskite films obtained in Example 1 and Comparative Example 1 are as follows: Figure 6 As shown, the synergistic passivation of the two ionic liquid additives significantly improved the crystalline quality of the perovskite film.

[0088] In summary, the present invention reduces the disorder of the Pb-I structure by utilizing the π-π interaction between the imidazolium cation and the 1-butyl-3-methylimidazolium cation to enhance the interaction between the cation and the perovskite Pb-I framework, effectively inhibiting the formation of unfavorable intermediate phases during the perovskite crystallization process. The method effectively eliminates the occurrence of stacking defects during the transformation of the δ-perovskite intermediate to the α-perovskite, thereby ensuring that the α-perovskite has a lower defect density and excellent photoelectric properties. The method is simple to operate, easy to implement, and has good application prospects.

[0089] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A perovskite solar cell based on a mixed ionic liquid additive, the cell being a PIN structure, comprising, from bottom to top, a transparent conductive substrate (1), a hole transport layer (2), a perovskite light absorption layer (3), an interface modification layer (4), an electron transport layer (5), a buffer layer (6) and a metal electrode (7); the band gap of the perovskite solar cell is 1.6 to 1.72 eV; The perovskite light absorbing layer (3) satisfies the following conditions at the same time: The perovskite light absorption layer (3) is an organic-inorganic hybrid multi-halogen mixed perovskite; The thickness of the perovskite light absorbing layer (3) is 500nm-1μm; The additives are imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, which are introduced into the perovskite precursor solution to passivate the perovskite bulk phase.

2. The perovskite solar cell according to claim 1, characterized in that: The transparent conductive substrate (1) is selected from one of FTO conductive glass and ITO conductive glass.

3. The perovskite solar cell according to claim 1, characterized in that: The material of the hole transport layer (2) is selected from self-assembled monolayer, P3CT-N, NiO x One or more organic or inorganic hole transport materials; The self-assembled monolayer comprises one or more of (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, (2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid (2-(7H-dibenzocarbazole-7-yl)ethyl)phosphonic acid self-assembled monolayer.

4. The perovskite solar cell according to claim 1, characterized in that: The material of the electron transport layer (5) is selected from [6,6]phenyl C61-butyric acid methyl ester PC 61 BM, Fullerene C 60 One of them.

5. The perovskite solar cell according to claim 1, characterized in that: The interface modification layer (4) comprises one or more of PEAI, MAI, bis(2-hydroxyethyl)dimethylammonium chloride BDAC, and choline chloride.

6. The perovskite solar cell according to claim 1, characterized in that: The material of the buffer layer (6) is selected from one of bathocuproin (BCP) and SnO2.

7. The perovskite solar cell according to claim 1, characterized in that: The metal electrode (7) satisfies the following conditions simultaneously: The metal electrode (7) is a metal electrode prepared by a thermal evaporation process; The thickness of the metal electrode (7) is 50-120 nm.

8. The method for preparing a perovskite solar cell according to any one of claims 1 to 7, characterized in that: The method for preparing the perovskite absorption layer is a one-step doctor blade coating method, wherein an ionic liquid additive is mixed, including imidazole acetate and 1-butyl-3-methylimidazolium tetrafluoroborate, and introduced into a perovskite precursor solution to passivate the perovskite bulk phase, and a wet film of the perovskite absorption layer is prepared by the one-step doctor blade coating method, and annealing is performed to obtain a perovskite light absorption layer; The preparation method of the additive comprises: mixing imidazolium acetate and 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquids with a perovskite precursor solution; The solvent in the perovskite precursor solution is one or more of dimethylformamide, methyl pyrrolidone, and dimethyl sulfoxide; The solute in the perovskite precursor solution is one or more of CsI, MAI, FAI, PbI2, and PbBr2.

9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: In the scraping operation, the nitrogen purge pressure is set to 0.15-0.2Mpa; The annealing operation has an annealing temperature of 100 to 150° C. and an annealing time of 20 to 30 minutes.

10. Use of the perovskite light absorption layer prepared by the method according to claim 8 or 9, characterized in that: Applicable to perovskite-based tandem solar cells, including at least the following structural devices: 1) Inorganic perovskite / perovskite tandem solar cells; 2) Inorganic perovskite / crystalline silicon tandem solar cells; 3) Inorganic perovskite / copper indium gallium selenide tandem solar cells.

Citation Information

Patent Citations

  • Repairing agent and repairing method thereof and method for preparing photoelectric film

    CN111435705A

  • Perovskite crystalline silicon laminated solar cell and preparation method thereof

    CN116249416A

  • Low-temperature perovskite solar cell and preparation method thereof

    CN116828944A

  • Method for preparing solar cell with assistance of (trifluoroacetyl) benzotriazole

    CN117615622A

  • Long-term stable optoelectronic device

    WO2020109787A1